Derivative cash flows and corporate investment - Jankensgård, Håkan; Moursli, Reda M. (Journal of Banking & Finance, 2020)
According to an influential argument, corporate hedging supports corporate investment when internal cash flows are volatile and external financing is costly (Froot, Scharfstein and Stein, 1993). Despite its vast influence, the predictions of this theory have not yet been directly tested using actual derivative cash flows. This study uses hand-collected data on cash flows from derivative positions in the oil and gas industry between 2000 and 2015. Strikingly, on average, an extra dollar in derivative cash flows translates into one more dollar in capital expenditure. During industry recessions, the median ratio of derivative cash flows to capital expenditure rises to 20% for hedging firms, suggesting that derivatives play a crucial role in sustaining investment when the cost of external financing rises abruptly.